ED95 of remimazolam in nasal administration for attenuating preoperative anxiety in children - Long, Xiang; Wen, Li-xia; Yang, Hu; Zhu, Guo-hong; Zhang, Qing-yun; Jiang, Jing-jing; Gong, Yuan (Frontiers in Medicine, 2023)
Background: Preoperative anxiety often prevails in children at higher levels than adults, which is a common impediment for surgeons and anesthesiologists. It is of great necessity to explore an appropriate medication to improve this situation. Remimazolam, a kind of benzodiazepine drug, has been indicated for the induction and maintenance of procedural sedation in adults since 2020. To date, rare studies were reported to investigate the effect of Remimazolam on children. In this study, we investigated the safety and efficacy of intranasal drops of remimazolam, and tried to determine the 95% effective dose （ED95） of remimazolam in single intranasal administration in attenuating preoperative anxiety in children. Methods: In this study, 114 children were enrolled from January, 2021 to December, 2022, who underwent laparoscopic high-level inguinal hernia ligation, and divided into early childhood children group and pre-school children group. The biased coin design (BCD) was used to determine the target doses. Positive response was defined as the effective relief of preoperative anxiety (modified Yale Preoperative Anxiety Scale, mYPAS＜30). The initial nasal dose of remimazolam was 0.5 mg·kg-1 in the two groups. An increment or decrement of 0.1 mg·kg-1 was applied depending on the sedative responses. Isotonic regression and bootstrapping methods were used to calculate the ED95 and 95% confidence intervals (CIs), respectively. Results: 80 children completed the study, including 40 in the early childhood group and 40 in the pre-school children group. As statistical analysis indicated, the ED95 of single intranasal infusion of remimazolam for relief of preoperative anxiety is 1.57 mg·kg-1 (95%CI:1.45－1.59 mg·kg-1) in early childhood and 1.09 mg·kg-1 (95%CI: 0.99－1.11 mg·kg-1) in pre-school children, and the CIs did not overlap each other. Conclusions: Remimazolam is an effective medication to relieve preoperative anxiety in children. And the ED95 of single nasal administration of remimazolam for effective relief of preoperative anxiety was 1.57 mg·kg-1 and 1.09 mg·kg-1, respectively, in early childhood children and pre-school children.